Pembuatan Papan Penunjuk Arah Sebagai Fasilitas Penunjang Penanda Lokasi Destinasi Wisata di Desa Wisata Kembang Kuning, Kecamatan Sikur, Lombok Timur - Nuryunia Astuti; Yusrini Hidayati; Muhammad Jimli Assidiqi; Faturrahman (Universitas Mataram, 2022)
The Kembang Kuning tourism village has a diversity of natural resources and local culture which is one of the advantages of the village as a tourist attraction. Limited supporting facilities are one of the obstacles for tourists to visit the Kembang Kuning village tourist spot. The purpose of this activity is to design and make elegant signposts to be placed in tourist spots in Kembang Kuning Village. The activity stages include discussions and equalization of perceptions with tourism awareness groups, surveys of tourist spots, design, manufacture and installation of signposts. The results of the discussion agreed that the signposts were made in 2 categories, namely the signposts that were placed in each hamlet and the signposts that were installed at the tourist sites. The signposts for each hamlet are only made of 1 plank with a 1-way wood motif, while the signboards for tourist spots are made of several wooden patterned boards and contain some basic information on the relevant tourist spots. The signposts have been installed at 28 points. The presence of these signposts is expected to be useful for visiting tourists and make it easier for them to get information about the location of the tourist attraction to be addressed